Yaw Stability Control of EV based on Torque Distribution - 丁惜瀛; 张钦爽; 覃艳丽; 苑克臣 (Kongzhi Yu Xinxi Jishu)
The driving posture and trajectory of four-wheel-drive EV in the process of turning can not track orders of drivers just based on differential control, because the variable factors like road and tyre will cause some instability problems such as overswing, sideslip, oversteering and understeer. In order to solve these instability problems, after analyzing the relations between yaw rate and stability, it proposes direct yaw control strategy based on torque distribution, in-wheel motor is controlled with direct torque control(DTC) to high dynamic traction and conducted the simulation under Matlab/Simulink environment. The simulation result shows that the dynamic optimization of the tire torque distribution can control the vehicle attitude in the best range to ensure stability of the vehicle in the predetermined direction.